When Self-Doubt Sours Sweetness: Low Self-Esteem Undermines Romantic Partners' Sacrifices - Anderson, Joanna (University of Waterloo, 2012)
The partners of people with low self-esteem (LSEs) are just as loving and generous as the partners of people with high self-esteem (HSEs; Campbell, Simpson, Boldry, & Kashy, 2005; Murray et al., 2000). Nonetheless, LSEs persist in underestimating their partners’ regard (e.g., Murray, Holmes, & Griffin, 2000). In this research, I propose a model of attribution inversion, which predicts that LSEs will invert the positive attributions for a partner’s sacrifice that would be predicted by classic theory (Kelley, 1967), because of the risk associated with interpreting a partner’s sacrifice too positively. In Study 1, LSEs worried more than HSEs about their partners’ sacrifices. In Studies 2 and 3, LSEs experienced more anxiety over a large (but not small) sacrifice relative to HSEs, and attributed less caring motives to their partners. Studies 4 and 5 demonstrated my proposed mechanisms: Offering one’s partner an exchange of favors (Study 5)—thereby reducing exchange concerns—or experimentally increasing LSEs’ caring attributions (Study 4) eliminated LSEs’ tendency to be more cautious than HSEs about their partners’ sacrifices, suggesting that exchange concerns and doubts about caring drive LSEs’ typical caution. Finally, Study 6 demonstrated that caution is not unique to LSEs. Under a cognitive load manipulation, HSEs were just as cautious, but were apparently able to override that automatic inclination when given sufficient time and resources. Overall, my research suggests that the discounting of a partner’s sacrifices is one route by which low self-esteem is self-perpetuating even with a loving partner.
Keywords: self-esteem; relationships; Psychology